The Future of Water in African Cities : Why Waste Water? Diagnostic of Urban Water Management in 31 Cities in Africa, Companion Volume - Closas, Alvar; Naughton, Meleesa; Jacobsen, Michael (World Bank, Washington, DC, 2013)
By 2030, Africa's urban population will double, and the difficulties African cities currently face in providing sustainable water services will be exacerbated. 'The future of water in African cities: why waste water?' argues that the traditional approach of one source, one system, and one discharge cannot close the water gap. A more integrated, sustainable, and flexible approach, which takes into account new concepts such as water fit to a purpose, is needed in African cities. The book provides examples of cities in Africa and beyond that have already implemented Integrated Urban Water Management (IUWM) approaches both in terms of technical and institutional solutions. Case studies explore the ways in which IUWM can help meet future water demand in African cities. Recent work carried out by Bahri (2012) on IUWM for the Global Water Partnership has also emphasized the necessity to examine the challenges posed by urban sprawl for urban planners and to recognize the need for coordinate, response, and sustainable resource management across sectors, sources, services and scales. The World Bank has recognized a need for an integrated approach to urban water management. As part hereof the issue has come to the forefront: What is the specific character of the water challenge in African cities and how can we compare the severity of the challenge, the need for integrated approach and the local capacity to respond to these challenges? The study presented in this companion volume is an initial attempt to answer this question.